Customer satisfaction,commitment and loyalty: key variables for successful customer centricity in business-to-business market focus on MNC-a study in Telekom Malaysia Berhad (TM), Ipoh Perak / Hazwani Mohd Hatar - Mohd Hatar, Hazwani (Faculty of Business and Management, 2009)
This research is to study about customer satisfaction, commitment, and loyalty on the successful of customer centricity in business-to-business market focus on MNC. The study was conducted in one of the telecommunication company, which is Telekom Malaysia Berhad, specifically in EGS Perak department. The main problem is the level of customer centricity by the company, which will affect their business performance. Due to the problems, there are certain circumstances why the research objective was developed. First, is to study level of customer centricity in EGS, Perak. Next, is to determine the level of customer satisfaction, commitment, and loyalty in EGS, Perak and the last objective is to identify the relationship between customer satisfaction, commitment, and loyalty towards customer centricity. The findings of the research state that all variables, customer satisfaction, commitment and loyalty have a strong relationship with customer centricity and lead to the successful customer centricity. Besides, the result also illustrate that all variables which are customer satisfaction, commitment, loyalty and customer centricity are at moderate level. Overall, based on the finding, there are several recommendations that have been suggested in order to help or to improve the customer centricity in EGS department and TM as a whole. The organization should improve the service quality and products, in order to obtain customer satisfaction, build loyalty among the customer and improve commitment level.